Early history and distribution of trade ceramics in Southeast Asia. (16th May 2016) - Witkowski, Terrence H.
Abstract : Purpose: This paper aims to investigate the history and distribution of trade ceramics in Southeast Asia over a thousand-year period stretching from the ninth to the early nineteenth century CE. Design/methodology/approach: The study takes a material culture approach to the writing of marketing history by researching the ceramics trade from the starting point of artifacts and their social context. It draws from literatures on Chinese and Southeast Asian ceramics art history and archaeology. It also is informed by first-hand experience inspecting surviving artifacts in shops, talking to dealers and taking in museum displays. Findings: After a brief historical overview of the ceramics trade in Southeast Asia, the research further explores topics in physical distribution (transportation routes, hubs and local marketplaces and ships, cargo and packing) and product assortments, adaptation and globalization of consumer culture. Research limitations/implications: The art history and archaeological literatures provide a good overview of the ceramics trade and analysis of surviving material artifacts, but only limited information about distribution and consumption. Many questions remain unanswered. Originality/value: This study contributes to international business and marketing history by documenting a thousand years of trade among China, mainland and insular Southeast Asia, and a long-standing cultural exchange facilitated by seaborne commerce. It also shares a marketing perspective with the fields of Southeast Asian art history and archaeology. Research in marketing history has neglected this region. To fully understand the development of marketing in the pre-industrial era, accounts from civilizations outside the West must be included.